2018
DOI: 10.1364/ol.43.005484
|View full text |Cite
|
Sign up to set email alerts
|

Three-photon light-sheet fluorescence microscopy

Abstract: We present the first demonstration of three-photon excitation light-sheet fluorescence microscopy. Light-sheet fluorescence microscopy in single-and two-photon modes has emerged as a powerful wide-field, low photo-damage technique for fast volumetric imaging of biological samples. We extend this imaging modality to the three-photon regime enhancing its penetration depth. Our present study uses a standard conventional femtosecond pulsed laser at 1000 nm wavelength for the imaging of 450 µm diameter cellular sph… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 22 publications
2
23
0
Order By: Relevance
“…A quadratic signal enhancement is obtained in the case of 3PEF, corresponding to 64-fold more signal at f = 10 MHz (Fig. S3) compared to previously reported 3P-SPIM at f = 80MHz [29].…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A quadratic signal enhancement is obtained in the case of 3PEF, corresponding to 64-fold more signal at f = 10 MHz (Fig. S3) compared to previously reported 3P-SPIM at f = 80MHz [29].…”
Section: Discussionsupporting
confidence: 51%
“…As a consequence, nonlinear signals used in multiphoton light-sheet microscopy, such as 2-photon excited fluorescence (2PEF [4,24,27,28]), second harmonic generation (SHG [30]) or 3-photon excited fluorescence (3PEF [29]) can be enhanced by increasing T while keeping P mean constant. Using 2P-SPIM imaging zebrafish embryos expressing mCherry fluorescent proteins, KTP nanocrystals [30], and fluorospheres embedded in a gel (Supplementary methods and Table S1), we confirmed that both 2PEF and SHG signals depend linearly on T (n = 2, Fig.…”
Section: Two-and Three-photon Excited Fluorescence Increases With Lowmentioning
confidence: 99%
See 1 more Smart Citation
“…As a general tendency, seen from the 2PEF and 3PEF images in 3AD, 3PEF images are much sharper and show a much higher contrast compared to their 2PEF counterparts. This finding agrees well with the earlier threephoton imaging studies [3][4][5][6][7].…”
Section: Resultssupporting
confidence: 94%
“…In their seminal work, Horton et al have shown that microscopy based on three‐photon‐excited fluorescence (3PEF) enables a noninvasive, high‐resolution in vivo imaging of subcortical structures within an intact mouse brain. Significant recent milestones in the development of 3PEF imaging technology include demonstration of optical imaging of neuronal activity deep in intact mouse brain , wide‐field three‐photon optogenetic stimulation , brain structure and function detection through an intact skull , and 3PEF light‐sheet microscopy .…”
Section: Introductionmentioning
confidence: 99%